Monitoring the Remodeling of Biohybrid Tissue‐Engineered Vascular Grafts by Multimodal Molecular Imaging. Issue 10 (4th February 2022) - Rama, Elena; Mohapatra, Saurav Ranjan; Melcher, Christoph; Nolte, Teresa; Dadfar, Seyed Mohammadali; Brueck, Ramona; Pathak, Vertika; Rix, Anne; Gries, Thomas; Schulz, Volkmar; Lammers, Twan; Apel, Christian; et al.
Abstract: Tissue‐engineered vascular grafts (TEVGs) with the ability to grow and remodel open new perspectives for cardiovascular surgery. Equipping TEVGs with synthetic polymers and biological components provides a good compromise between high structural stability and biological adaptability. However, imaging approaches to control grafts' structural integrity, physiological function, and remodeling during the entire transition between late in vitro maturation and early in vivo engraftment are mandatory for clinical implementation. Thus, a comprehensive molecular imaging concept using magnetic resonance imaging (MRI) and ultrasound (US) to monitor textile scaffold resorption, extracellular matrix (ECM) remodeling, and endothelial integrity in TEVGs is presented here. Superparamagnetic iron‐oxide nanoparticles (SPION) incorporated in biodegradable poly(lactic‐ co ‐glycolic acid) (PLGA) fibers of the TEVGs allow to quantitatively monitor scaffold resorption via MRI both in vitro and in vivo. Additionally, ECM formation can be depicted by molecular MRI using elastin‐ and collagen‐targeted probes. Finally, molecular US of α v β 3 integrins confirms the absence of endothelial dysfunction; the latter is provocable by TNF‐ α . In conclusion, the successful employment of noninvasive molecular imaging to longitudinally evaluate TEVGs remodeling is demonstrated. This approach may foster its translation from in vitro quality control assessment to in vivo applications to ensure proper prostheses engraftment. Abstract : Noninvasive imaging modalities are fundamental to control the remodeling and function of biohybrid tissue‐engineered vascular grafts, which is particularly true for the critical transition time between late in vitro maturation and early in vivo engraftment. Here, a noninvasive multimodal, molecular imaging concept is presented to longitudinally monitor textile scaffold resorption, extracellular matrix remodeling, and endothelial inflammation.